2022
DOI: 10.1002/jbio.202200186
|View full text |Cite
|
Sign up to set email alerts
|

Impact of temperature on optical sensing in biology based on investigation of SARS‐CoV‐2

Abstract: In this paper, we present an investigation of the influence of the temperature on the sensing of biological samples. We used biofunctionalized microsphere‐based fiber‐optic sensor to detect immunoglobulin G attached to the sensor head at temperatures relevant in biological research: 5°C, 25°C, and 55°C. The construction of the sensor allowed us to perform measurements in the small amount of solution. The results of our experiment confirm substantial changes in the measured reflected optical power, indicating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…By providing reliable and precise measurements, our research emphasizes the critical role of temperature management in ensuring accurate analysis of biological samples and underscores the utility of advanced sensing technologies in biomedical applications. 20…”
Section: Methodsmentioning
confidence: 99%
“…By providing reliable and precise measurements, our research emphasizes the critical role of temperature management in ensuring accurate analysis of biological samples and underscores the utility of advanced sensing technologies in biomedical applications. 20…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, we present the method of discriminating urinary tract infections from urinary tract infections capable of causing urosepsis. The proposed method is based on absorption, allowing the determination of the changes in radiation intensity, similar to the solutions previously described by us [26,27]. The amount of absorbed radiation depends on the concentration [28] and the presence of secreted metabolites, and proteins by bacteria in each supernatant from the urine patient's sample.…”
Section: Introductionmentioning
confidence: 99%
“…A topic that could not be forgotten is the application of biophotonics methods to detect the SARS‐CoV2 virus. In a paper that covers this topic, the group of Professor Malgorzata Szczerska presents the design and discusses the principle of operation of a SARS‐CoV2 biophotonic sensor [2]. This sensor, which is based on a single‐mode telecommunication fiber, is able to detect the SARS‐CoV2 specific immunoglobulin G (IgG) antibodies.…”
mentioning
confidence: 99%
“…Szczerska et al analyze the impact of temperature on the optical sensing of IgG antibodies to investigate SARS‐CoV2 virus [6]. By using a microsphere‐based fiber‐optic sensor to detect IgG at temperatures of 5, 25, and 55°C, it was observed that substantial changes in the reflected optical power are induced by the temperature change.…”
mentioning
confidence: 99%